Multiparty Session Types, Beyond Duality (Abstract) - Alceste Scalas (Electronic Proceedings in Theoretical Computer Science, 2017)
Multiparty Session Types (MPST) are a well-established typing discipline for message-passing processes interacting on sessions involving two or more participants. Session typing can ensure desirable properties: absence of communication errors and deadlocks, and protocol conformance. However, existing MPST works provide a subject reduction result that is arguably (and sometimes, surprisingly) restrictive: it only holds for typing contexts with strong duality constraints on the interactions between pairs of participants. Consequently, many "intuitively correct" examples cannot be typed and/or cannot be proved type-safe. We illustrate some of these examples, and discuss the reason for these limitations. Then, we outline a novel MPST typing system that removes these restrictions.